Integrative proteomics and metabolomics of Guizhou Miao Sour Soup affecting simple obese rats - Yuan, Qin; Zhou, Qianqian; Wang, Nanlan; Zheng, Yuancui; Hu, Hua; Hu, Shiyao; Wang, Huiqun (Frontiers in Nutrition, 2022)
Miao Sour Soup (MSS) is a fermented product from the Qiandongnan region of Guizhou Province, which enrich many beneficial ingredients and is widely consumed in the whole China. Fermented food is beneficial to physical health with the potential positive regulating affection on simple obesity. In this study, we analyzed the mechanism of action of MSS to prevent simple obesity induced by high-fat diet by proteomics and metabolomics. Quantitative proteomics with tandem mass tagging labeling and liquid chromatography-mass spectrometry was used to analyze the changes of liver proteins and metabolites after the MSS intervention. MSS intervention upregulated 33 proteins and 9 metabolites and downregulated 19 proteins and 10 metabolites. Bioinformatics analysis showed that MSS could prevent simple obesity by acting on the PPAR signaling pathway, Retinol metabolism, Fatty acid β-oxidation, Fatty acid degradation, Fatty acid biosynthesis, Glycine, serine and threonine metabolism, Pyruvate metabolism, Citrate cycle (TCA cycle) and other signaling pathways. This study provides new insights into the use of MSS to prevent simple obesity caused by high-fat diets and the search for healthy eating patterns with MSS.